US defence policy: Between isolationism and the pursuit of dominance. Contradictions in Washington demand a clear response from Europe - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2026)
US defence policy is characterised by contradictions that are on display once again in the Trump administration's latest strategy documents. The reasons for this go far beyond the president's erratic behaviour. At the core lies the unanswered question of how the United States should deal with the loss of global dominance. For Europe, these contradictions present not only risks but also opportunities. But German and European decision-makers should not fall victim to the false hope that NATO in its current form will survive Trump's second term in office.
Keywords: 320; Westliche Hemisphäre; National Security Strategy; NSS; National Defense Strategy; NDS; Pete Hegseth; unipolar moment; Isolationism; Monroe Doctrine